El sinsentido como problema hermenéutico en el fenómeno de las nuevas tecnologías (2009)
This article shows how the concept of oblivion of Being (Seinsvergessenheit) developed in the first phase of Heidegger’s work can be applied to its second phase in which he discusses the phenomenon of technique. The phenomenon of the new technologies will be discussed from Heidegger’s perspective on the Question to Technology. In other words, it will attempt to show how the German thinker applies his hermeneutics to present the problem of the sense nonsense in the phenomenon of technology.